Restoration of Upper Limb Function in an Individual with Cervical Spondylotic Myelopathy using Functional Electrical Stimulation Therapy: A Case Study - Popovic, Milos R.; Zivanovic, Vera; Valiante, Taufik A. (Frontiers in Neurology, 2016)
Non-traumatic spinal cord pathology is responsible for 25–52% of all spinal cord lesions. Studies have revealed that spinal stenosis accounts for 16–21% of spinal cord injury (SCI) admissions. Impaired grips as well as slow unskilled hand and finger movements are the most common complaints in patients with spinal cord disorders, such as myelopathy secondary to cervical spondylosis. In the past, our team carried out couple of successful clinical trials, including two randomized control trials, showing that functional electrical stimulation therapy (FEST) can restore voluntary reaching and/or grasping function, in people with stroke and traumatic SCI. Motivated by this success, we decided to examine changes in the upper limb function following FEST in a patient who suffered loss of hand function due to myelopathy secondary to cervical spondylosis. The participant was a 61-year-old male who had C3–C7 posterior laminectomy and instrumented fusion for cervical myelopathy. The participant presented with progressive right hand weakness that resulted in his inability to voluntarily open and close the hand and to manipulate objects unilaterally with his right hand. The participant was enrolled in the study ~22 months following initial surgical intervention. Participant was assessed using Toronto Rehabilitation Institute’s Hand Function Test (TRI-HFT), Action Research Arm Test (ARAT), Functional Independence Measure (FIM), and Spinal Cord Independence Measure (SCIM). The pre–post differences in scores on all measures clearly demonstrated improvement in voluntary hand function following 15 1-h FEST sessions. The changes observed were meaningful and have resulted in substantial improvement in performance of activities of daily living. These results provide preliminary evidence that FEST has a potential to improve upper limb function in patients with non-traumatic SCI, such as myelopathy secondary to cervical spondylosis.